Edukasi Pelaporan Keuangan Koperasi Berdasarkan Standar Akuntansi Keuangan Entitas Privat (SAK EP) - Kamil, Islamiah; Istianingsih; Yolifiandri; Anjarwati, Sri; Irawan, Indra Ade (Politeknik Penerbangan Indonesia Curug, 2025)
Cooperative Financial Reporting Education Based on the Financial Accounting Standards for Private Entities (SAK EP) is an important step in improving the transparency, accountability, and governance of cooperatives. This standard is designed to ensure that cooperative financial statements are prepared with accounting principles that are accurate, relevant, and comparable, thus supporting better decision-making by stakeholders. This community service program aims to increase the understanding of cooperative members, administrators, and other stakeholders on the importance of implementing SAK EP. This activity includes socialization, training, as well as in-depth discussions to identify challenges in the implementation of this accounting standard. Some of the barriers often encountered in its implementation include a lack of accounting understanding, limited human resources, and resistance to changes in the financial reporting system. Therefore, the program also focuses on compliance improvement strategies, such as continuous training, technical assistance, and provision of adequate resources for cooperatives. It is expected that with this education and assistance, cooperatives can prepare more transparent and accurate financial statements, increasing credibility in the eyes of members and other stakeholders. Effective implementation of SAK EP not only strengthens the financial stability of cooperatives but also encourages economic growth based on justice and togetherness. With better reporting, cooperatives can attract more investment, increase access to financing, and strengthen public confidence in the cooperative system in Indonesia.